Design and Implementation of Real Time Charging Optimization for Hybrid Electric Vehicles - K. Ramesh; C. Bharatiraja; S. Raghu; G. Vijayalakshmi; PL. Sambanthan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
Electric vehicle (EV) has gained incredible interest from the past two decade as one of the hopeful greenhouse gasses solution. The number of Electric Vehicle (EV) is increasing around the world; hence that making EVs user friendly becomes more important. The main challenge in usage of EV is the charging time required for the batteries used in EV. As a consequence, this subject matter has been researched in many credentials where a wide range of solutions have been proposed. However those solutions are in nature due to the complex hardware structure. To provide an unswerving journey an Android application based charging optimization is proposed. This application is aimed at giving relevant information about the EV’s battery state of charge (SOC), accurate location of the EV, booking of the charging slots using token system and route planner. At emergency situations, an alternative service is provided by mobile charging stations. Route planner indicates the temperature by which prediction of reaching the destination can be done. In addition to that nearest places such as parks, motels are indicated. The estimated time and distance between the electric vehicle and the charging station is calculated by the charging station server according to which the parking lot is allocated. Vehicle to charging station communication is established for the time estimation of charging. This will help the EV users to know about charge status and charging station, which support fast charging method and availability of the station on the go and also when to charge their EV. The Arduino UNO board has been used for the hardware part. The hardware results are confirming the conceptual of the proposed work.